Is mixed reality technology an effective tool for retail? A vividness and interaction perspective - Gil-López, Cristina; Guixeres, Jaime; Marín-Morales, Javier; Torrecilla, Carmen; Williams, Edu; Alcañiz, Mariano (Frontiers in Virtual Reality, 2023)
There is increasing interest in studies analyzing the influence of technologies that integrate virtual and real-world components on consumer behavior. These technologies include augmented reality (AR), virtual reality (VR) and mixed reality (MR). Mixed reality (MR) is a user environment in which physical reality and digital content are combined in a way that enables interaction with and among real-world and virtual objects. In spite of previous works related with MR and retails spaces, little is known about how consumers respond to MR features and which elements of the MR-based experience, such as vividness and novelty, impact behavior. In this study, we have explored the relative advantage of mixed reality in retail shopping practices over a traditional-based purchase. Implicit reactions of shoppers when interacting with products with and without MR glasses were compared. The results reveal that participants wearing MR glasses exhibited different patterns of interaction (i.e., frequency and interaction with product duration) that differed from those indicated by participants who did not wear the MR technology. At the level of purchase decision, our results show that the use of MR smart glasses has an impact on decision times that relates to a utilitarian purchase type. Based on participants´ explicit answers to questionnaires, the reported findings further show that the perceived hedonic and utilitarian values of the purchase experience were higher when MR was used, which also affected future purchase intentions and perceived emotional state as reported by consumers' experience and satisfaction in the context of retail.